European transnational migration and homelessness in Scandinavia. Issue 1 (6th March 2017) - Amundson, Erik
Abstract : Purpose: The purpose of this paper is to examine the European transnational migration of poverty in a regional context, specifically focusing on homelessness among the migrant poor in Norway and Sweden. Gathering insight from individuals who routinely assist with social care, this research seeks to find out if the liberal provision of welfare and supportive services attracts poor migrants to this region from other parts of Europe. Design/methodology/approach: Qualitative in-depth interviews with individuals who provide social care assistance to homeless migrants in Oslo and Stockholm. Findings: The influx of people experiencing homelessness in these areas is comprised mainly of two distinct sub-populations. One group migrated in search of employment opportunities but struggled with tenuous working and living arrangements. A second more transient group appeared to be motivated by perceptions of Scandinavian benevolence and charity. Both groups lacked familiarity with the social welfare system but were generally uninhibited by cultural differences between their destination and country of origin. Research limitations/implications: The intent of this study is not to generalize to a broader population but to develop an in-depth exploration of homelessness and migration from the perspective of social care workers. Purposive sampling is used to gather insights from key informants that work closely with homeless migrants; however the findings can be limited by the unique experiences of each individual. Practical implications: In the public discourse on homelessness it is a mistake to group all homeless migrants together. Additionally it is important to distinguish between the needs of migrants and non-migrants, as these two homeless populations generally do not struggle with the same issues. Originality/value: With a better understanding of this issue, governments will be able to provide more adequate assistance and develop more effective initiatives to combat and prevent homelessness.